Legal Review of the Implementation of the Investigation System for Money Laundering Crimes - Muhammad Al Huda; Gunarto Gunarto (Jurnal Hukum Khaira Ummah, 2025)
Abstract. From a legal political perspective, money laundering has become a crucial link in the crime chain. The Law on the Prevention and Eradication of Money Laundering does not have a comprehensive special procedural law, although money laundering is classified as a serious crime under Law Number 1 of 2023 concerning the Criminal Code (KUHP). Other serious crimes, such as terrorism, narcotics, or corruption, have special procedural laws that clarify the series of activities investigators must undertake to establish evidence. The aim of this research is to find out and analyze (1) the elaboration of the development of money laundering crimes globally and nationally, (2) the system for investigating money laundering crimes from a legal perspective, (3) legal problems in efforts to investigate money laundering crimes. The approach method used in this research is normative juridical. The specifications of this research are analytical descriptive. The data source used is secondary data. Secondary data is data obtained from library research consisting of primary legal materials, secondary legal materials and tertiary legal materials. The research results and discussion can be concluded: (1) In the history of business law, the emergence of money laundering began in the United States since 1930. The centers of large gangsters who were skilled at money laundering in the United States were known as the legendary group Al Capone (Chicago). In the national scope, Indonesia only viewed the practice of money laundering as a crime and set sanctions for the perpetrators when Law No. 15 of 2002 concerning money laundering was enacted. (2) The crime of money laundering is a crime that arises from a previous crime or a subsequent crime. The investigation system with a special method which is the interpretation of the scheme for starting the investigation of the crime of money laundering is Parallel Investigation, Independent Investigation, and Further Investigation. (3) The existence of disparities in interpretation of the provisions of the Law on the Crime of Money Laundering will have implications for many perpetrators of the crime of money laundering who have the potential to be free/escape from legal prosecution. This is because from the perspective of law enforcement, the actions carried out by the perpetrators are not Money Laundering Crimes because there is not perfect placement, layering and integration, or the fraudsters are considered not to fulfill the element of knowing or suspecting "assets resulting from crime".